1998
DOI: 10.1097/00006534-199812000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Second Intention Wound Healing by Emu Oil Lotion: Comparative Results with Furasin, Polysporin, and Cortisone

Abstract: Previous studies showed that twice-daily application of emu oil lotion (mixture of emu oil/fat, vitamin E, and botanical oil) immediately after creation of full-thickness skin defects delayed wound healing 6 days later, perhaps owing to its antiinflammatory actions. If administration was delayed for 48 hours, a two-fold promotion of wound contraction, epithelialization, and infiltration of organized granulation tissue was observed. In the present study, emu oil lotion was applied to full-thickness skin defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Emu oil was used by one specialist in this survey. There is evidence suggesting that emu oil, when combined with vitamin E, promotes faster healing with less pain and scarring in experimentally induced surgical wounds and burns in mice models, although further studies in dogs and people with ARID are needed 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…Emu oil was used by one specialist in this survey. There is evidence suggesting that emu oil, when combined with vitamin E, promotes faster healing with less pain and scarring in experimentally induced surgical wounds and burns in mice models, although further studies in dogs and people with ARID are needed 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…Neither study evaluated tissue cytokine levels as biomarkers of inflammation. Two other studies looked at the anti-inflammatory and wound-healing properties of emu oil when applied topically (3,4).…”
mentioning
confidence: 99%
“…Emu oil mainly consists of several types of fatty acids, carotenoids, flavones, polyphenols, tocopherol, and phospholipids (Brown et al 1995). Several studies have indicated that emu oil reduces the inflammatory response by suppressing the expression of pro-inflammatory cytokines, resulting in reduced oxidative injury and rapid wound healing and recovery (Politis and Dmytrowich 1998;Yoqanathan et al 2003;Bennett et al 2008). The anti-inflammatory effect of emu oil in canine skin infection requires further investigation.…”
Section: Discussionmentioning
confidence: 99%